Effect of Microstructure on Mechanical Properties and Wear Characteristics of Cemented Tungsten Carbides - Sun, H; Irwan, R; Huang, H; Stachowiak, Gwidon (Trans Tech Publications, Switzerland, 2009)
The effect of microstructure of cemented tungsten carbide materials on their mechanical properties and wear characteristics was investigated using nano indentation and nanoscratch methods. The results indicated that the variation in grain size insignificantly affected the hardness, elastic modulus and friction coefficient of the work materials, but considerably influenced their removal rates. The carbide with coarser grains exhibited a much higher removal rate was obtained during scratching.